Application of Computational Programming Softwares In Teaching of Structural Analysis In Industry 4.0 Period - Van, Tran Thi Thuy (International Journal of Psychosocial Rehabilitation, 2020)
In Vietnam, nowadays, due to the requirement of changing the training program, it leads to a change in the teaching time of subjects in general and structural analysis in particular. In addition, with the development of information technology, the courses require the use of computational programming softwares to help students understand the nature of the subject matter and in a shorter time solving more complex problems without mathematical difficulties. Based on these requirements, the article introduces how to apply some computational softwares to teaching structural analysis and the analysis of advantages and disadvantages as well as the applicability of each software. Besides, the article introduces some subroutines established by the author to teach students in the parts of structural analysis.